Identifikasi Non-Added Value Activity Dalam Proses Pemeriksaan Substantif Permohonan Paten Menggunakan Value Stream Mapping - Muslim, Muslim; Ichwan, Muhammad Nur; Ikatrinasar, Ikatrinasar; Fitri, Zulfa (Journal of Industrial and Engineering System, 2022)
The process of substantive patent examination which is complicated and takes a long time is one of the reasons the inventor is "reluctant" to apply for a patent on his invention. This research was conducted using the Current State Value Stream Mapping (CSVSM) method, which began with the creation of a process flow map with the cycle time of each activity. It is known that most of the activities are value added activities. However, there is 1 activity that is required but not added value, namely the activity of verifying the technical field of application documents; and 1 non-value-added activity, namely initialing the Patent Granting letter. The number of waiting/delaying incidents is a waste in the process of substantive examination of patent applications caused by: (a) employees generally do double work; and (b) the absence of SOPs in each sub-process/sub-activity in the process of substantive examination of patent applications. Proposed improvements are submitted in the Future State Value Stream Mapping (FSVSM). As a result, lead-time can be reduced to 11 days, which was originally 26 days; and Process Cycle Efficiency which was originally 19.23% increased to 45.45%